Sosialisasi dan Identifikasi Tingkat Kepedulian Siswa SMA terhadap Bahaya Paparan Radiasi menggunakan Analisis Rasch - Ulya, Naily; Kusumadewi Kuncoro, Alvina; Hadiana Aminudin, Adam; Nur Syamsiah, Endah; Aningsih, Sri; Zikriani Ramdhani, Saumi; Nurhanivah, Devi; Bilqis, Ayesha; Rizka Taufani, Muhammad (PADMA, 2024)
To raise awareness among high school students about the risks associated with radiation exposure and gauge their level of worry, the Physics Study Program at Universitas Kebangsaan Republik Indonesia is organizing this event as a community service. 48 high school students from one of Majalaya's high schools—35 in science and 13 in social studies—participated in this activity. Five positive and five negative items were included in the Likert scale questionnaire that was utilized as the instrument. The Rasch analysis was used to find any potential biases and changes in the degree of concern for the risks of radiation exposure following socialization, and the N-gain analysis was used to find changes in that level of concern. Although the results are still low (N-gain = 0.23) and include remarks, they do indicate a shift in students' concerns over the risks of radiation exposure. First, according to the Rasch analysis, 17% of students are able to accurately respond to every statement. For the pretest and posttest, 50% and 70%, respectively, of the students can respond to every statement. Following their participation in socialization, it may be concluded that every student is aware of the risks associated with radiation exposure. Second, except from item number 10 and the suggestion that it should be revised, none of the assertions are biased against any of the groups